2008
DOI: 10.2169/internalmedicine.47.0499
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Stunned Myocardium Associated with Status Epileptics and Postictal Catecholamine Surge

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 18 publications
2
54
0
Order By: Relevance
“…The likely pre-mortem expression of this pathology, Takotsubo cardiomyopathy, has been observed after seizures and is associated with QT prolongation and T wave inversion: endocardial biopsy in these cases is consistent with myocytolysis with normal cardiac arteries present on angiography. Cardiac MIBG-scanning is consistent with increased cardiac sympathetic neural activity [65,66].…”
Section: Epilepsymentioning
confidence: 68%
“…The likely pre-mortem expression of this pathology, Takotsubo cardiomyopathy, has been observed after seizures and is associated with QT prolongation and T wave inversion: endocardial biopsy in these cases is consistent with myocytolysis with normal cardiac arteries present on angiography. Cardiac MIBG-scanning is consistent with increased cardiac sympathetic neural activity [65,66].…”
Section: Epilepsymentioning
confidence: 68%
“…TTC is not only common complication (25%) in the critically ill patients and in intensive care population [13;25-28] but also in subarachnoidal hemorrhage (33%) subjects [26;29;30]. It has been observed during epileptic seizures and may be the cause of sudden death in some cases [31]. A recent publication has suggested that TTC is an acute heart failure syndrome associated with a significant in-hospital death that is comparable with acute coronary syndrome patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that a left ventricular abnormality occurring with stress-induced cardiomyopathy might be secondary to a catecholamine surge that is brought on by intensely psychological or physical stress. Much of the evidence for this comes from observational and case-control studies that have found an association between elevated catecholamine levels and disease onset (13)(14)(15). More direct evidence for the role of catecholamine in disease pathogenesis was obtained from animal studies which have shown that iatrogenic administration of catecholamines or stress immobilization can lead to reversible left ventricular apical ballooning (16,17).…”
Section: Discussionmentioning
confidence: 99%